Mi Casa es Mi Casa: Women’s Navigation of Living Apart Together (LAT) Relationships in Sweden & Austria - Stockinger,Julia (2025)
On not sharing ones home with ones partner: The gendered experience of women in LAT relationships in Sweden and Austria. This thesis explores the gendered experiences of women in Living Apart Together (LAT) relationships. It focuses on how LAT as a relational form is negotiated within the contested space of intimacy and coupledom, that is shaped by cultural norms and societal expectations around cohabitation. Based on ethnographic fieldwork conducted in Austria nd Sweden between November 2024 and April 2025, including biographical interviews, participant observation, policy analysis, and autoethnographic reflections, the study examines what it means for women to claim and maintain a home on their own terms. To conceptualize LAT as a relational practice unfolding within a metaphorical space of intimacy - a space structured by social norms, affective orientations, and struggles over legitimacy and recognition - I draw on Pierre Bourdieu’s theory of practice - to trace how relational dispositions are formed and how they orient individuals toward dominant scripts such as cohabitation. As a complementing lens, this study is informed by feminist cultural theory, particularly Sara Ahmed’s work on the promise of happiness, which offers a critical perspective for understanding how normative ideals of intimacy are internalized and act on women's lived experiences. Finally, Erving Goffman’s dramaturgical model of frontstage and backstage visualizes what kinds of allowances LAT provides, particularly how it enables women to manage availability and set boundaries within the realm of intimate life. Findings highlight how LAT can serve as a form of autonomy enactment, allowing women to opt out of perceived unequal distributions of domestic labour experienced in previous cohabiting relationships. Space, both its presence and absence, emerges as an important axis around which intimacy, autonomy, and wellbeing are negotiated. By mapping these evolving geographies of relating, this thesis contributes new insights to feminist scholarship on intimacy, the anthropology of space, and the cultural analysis of late-modern relationship models. Beyond the academic realm, this thesis invites in space builders - such as architects, planners and policy makers - as LAT offers a lens for reimagining how intimacy, autonomy, and care might be better supported through the spaces we build and the policies we write.
Keywords: LAT; Living-Apart-Together; Särbo; intimate-relationships; home; anthropology-of-space; qualitative-research; non-cohabiting relationships; feminist-spatial- strategy; cultural analysis; love